Construction network compression programming - Chang, Hung-jen; Tongchat Hongladaromp; Morino, Shosuke (Bangkok : Asian Institute of Technology, 1975)
A construction project is represented by a network with activities on arrows. All activities can be randomly arranged and events randomly numbered without repetition prior to computer processing. Cost functions are assumed to be linear. A structural model composed of columns and plates is proposed to represent activities and events of corresponding network. An algorithm is presented based on the model. A computer program in FORTRAN IV is then developed to serve the following functions: a. Checking illegal conditions of a network described above, b. Reordering the sequence of input activities. c. Renumbering events of the network in ascending order. d. Performing critical path scheduling. e . Compressing the network to a required completion time. A desired schedule is obtained regarding its minimum project cost.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Structural engineering; Building -- Details